Enhancing Tomato Productivity and Quality in Moderately Saline Soils through Salicornia-Assisted Cultivation Methods: A Comparative Study - Marco Santin; Prangthip Parichanon; Maria Calogera Sciampagna; Annamaria Ranieri; Antonella Castagna (Horticulturae, 2024)
The presence of high salt in soils is a substantial abiotic constraint for agricultural activities worldwide, particularly in Mediterranean regions. Researchers have discovered a simple and efficient way to repair soils that have suffered from excessive salt use. They use plants that can overcome salt, like halophytes, to improve the soil quality. This research aimed to evaluate the tomato productivity and quality cultivated using different methods. We look at three different ways to grow tomatoes with the halophyte Salicornia europaea L. in a moderately salty soil: monoculture (only tomatoes), intercropping (mixed cultivation), and sequential cropping (growing tomatoes where halophytes were grown before). We considered how the different ways of managing crops affected tomato yield, biochemical factors in tomato plants (like phenolic and flavonoid contents), antioxidant levels, carotene profiles, and fruit quality and production. Sequential cropping showed the highest tomato productivity, while intercropping exhibited high concentrations of total phenolics, total flavonoids, carotenoids, and antioxidant capacity. The tomatoes had a sweet taste due to the higher total soluble solid content (TSSC) and maintained their quality due to the higher titratable acidity (TA).